A Strategy For The Development Of Superior Rice Seeds In Ogan Komering Ilir Regency - Andhini Koeswito, Winnie; Yazid, Muhammad; Riswani (Department of Agribusiness, Faculty of Science and Technology, UIN Syarif Hidayatullah Jakarta, 2025)
ABSTRACT Superior seed breeding is one of the food products that has the opportunity to be developed in an agribusiness system. This study aims to formulate a development strategy for superior rice seed breeding in Ogan Komering Ilir Regency. The selection of the research location uses purposive sampling method while the sample withdrawal uses non- probability sampling by taking a sample of breeder farmers in Bumi Agung Village, Lempuing District, OKI Regency. Rice seed breeder farmers in this village amounted to 60 people who were purposively selected as samples of this study. Primary data in this study were collected by means of a survey using a questionnaire and analyzed using SWOT. The results showed that superior rice seed breeding is in quadrant I, which has a position (S-O) seed breeding businesses can take advantage of internal strengths to seize external opportunities. alternative strategies that can be applied are optimizing internal strengths, namely farmer experience, effective management, and distribution networks that have been formed, in order to take advantage of external opportunities, such as increased market demand and potential cooperation with third parties. Keywords : development; rice seed; regulation.